The Effect of Vulva Hygiene Using Betel Leaf Decoction on Healing Perineal Wounds in Postpartum Women: Pengaruh Vulva Hygiene Menggunakan Rebusan Daun Sirih terhadap Penyembuhan Luka Perineum pada Ibu Nifas - Ainun, Ismi; Sumiaty, Sumiaty; Asriwidyayanti, Asriwidyayanti; Maineny, Arie; Hadriani, Hadriani; Pani, Widya (Napande: Jurnal Bidan, 2024)
Background: Perineal suture wounds caused by episiotomy and rupture, if not handled properly and correctly, can become a medium for germs to enter and can cause infection, the mother becomes feverish, and can even cause a foul odor from the vagina. Objective: to determine the effect of vulva hygiene using betel leaf decoction on the healing of perineal wounds in postpartum mothers in the Working Area of the Pantoloan Health Center, Palu City. Methods: This study used a quasi-experimental research type, with a sample of 20 people, 10 intervention people, and 10 control people, with a sampling technique using consecutive sampling. Univariate and bivariate analysis with Wilcoxon test. Results: The healing of perineal wounds in the intervention group all healed after being given betel leaf decoction, while the control group healed perineal wounds totaling 5 people and 5 people did not heal. Wilcoxon test with a p-value of 0.002 (< 0.05).  Conclusion: there is an effect of vulva hygiene using betel leaf decoction on the healing of perineal wounds in postpartum mothers in the Working Area of the Pantoloan Health Center, Palu City. It is recommended for health workers at the health center to provide vulva hygiene material to postpartum mothers during counseling.